PELATIHAN KEWIRAUSAHAAN DALAM MENDUKUNG PEMBERDAYAAN EKONOMI PEREMPUAN DI KECAMATAN BALEENDAH - Yuanita, Rahel; Nuraeni, Nuraeni (Universitas Padjadjaran, 2024)
This article discusses BTPN Syariah's community service initiative in the form of a student internship program, which is integrated with the government's 'Merdeka Belajar Kampus Merdeka' (MBKM) policy. The Bestee program carried out by BTPN Syariah involves students from various universities who are divided into several groups that focus on empowering women through mentoring the entrepreneurial skills of women aged 18-60 years who are BTPN Syariah customers from pre-prosperous backgrounds. These women receive skills and entrepreneurship training as well as access to financing sources to help them achieve financial independence. Students use active participation methods, such as interviews and documentation, to ensure that the business skills training is relevant to the needs of the participants. This program is useful for providing students with real experience in the business world, empowering women with entrepreneurial skills to achieve financial independence, and contributing to sustainable development goals related to financial inclusion, economic growth, and gender equality. This article is based on the results of an internship activity located in Baleendah District, Bandung Regency, West Java.Artikel ini membahas inisiatif pengabdian masyarakat BTPN Syariah dalam bentuk program magang mahasiswa, yang terintegrasi dengan kebijakan 'Merdeka Belajar Kampus Merdeka' (MBKM) oleh pemerintah. Program Bestee yang diusung oleh BTPN Syariah ini melibatkan mahasiswa dari berbagai perguruan tinggi yang terbagi dalam beberapa kelompok yang berfokus pada pemberdayaan perempuan melalui pendampingan keterampilan kewirausahaan perempuan berusia 18-60 tahun yang merupakan nasabah BTPN Syariah dari latar belakang pra-sejahtera. Para perempuan ini menerima pelatihan keterampilan dan kewirausahaan serta akses sumber pembiayaan untuk membantu mereka mencapai kemandirian finansial. Mahasiswa menggunakan metode partisipasi aktif, seperti wawancara dan dokumentasi, untuk memastikan pelatihan keterampilan usaha relevan dengan kebutuhan peserta. Program ini bermanfaat memberikan mahasiswa pengalaman nyata di dunia bisnis, memberdayakan perempuan dengan keterampilan kewirausahaan untuk mencapai kemandirian finansial, serta berkontribusi pada tujuan pembangunan berkelanjutan yang terkait dengan inklusi keuangan, pertumbuhan ekonomi, dan kesetaraan gender. Tulisan ini dibuat berdasarkan hasil kegiatan magang yang berlokasi di Kecamatan Baleendah, Kabupaten Bandung, Jawa Barat.